The relationship between empowerment and employee performance at Perbadanan memajukan Iktisad Negeri Terengganu (PMINT) / Nur Syahirah Mohd Zain - Mohd Zain, Nur Syahirah (2017)
The purpose of this study is to identify the relationship between empowerment and employee performance in a company or organization. The selected organization is Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT). This correlation research was to determine that there is an existence of correlation between independent variables and dependent variables. The independent variables are serving employee, monitoring employee, mentoring employee and coaching employee. The sampling frame is the staff at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) with the population of 220 staff. However, in this study based on sample size decided based on table Kerjcie and Morgan (1970) which for 220 populations provide 140 sample sizes by using stratified sampling. In addition, the internal consistency using Cronbach’s Alpha are also used to verify the measurement used later. The unit of analysis is individual with the instrument of five point Likert Scale question. Therefore, questionnaire is used to collect the data and Statistical Package for Social Science (SPSS) version 20.0 is used to compute the correlation of the variables. The objective of this study are to identify the empowerment factors that have been practiced by employee erformance at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) and to identify whether there is any relationship between empowerment and employee performance at Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT) . The result of the research shows that the independent variables are positive correlated with dependent variable thus the hypotheses were accepted. All the factors of empowerment have been practiced in Perbadanan Memajukan Iktisad Negeri Terengganu (PMINT). For the recommendations, the researcher gives suggestion to increase employees’ performance through empowerment.